PENGARUH JUMLAH OBJEK WISATA, JUMLAH WISATAWAN DAN TINGKAT HUNIAN HOTEL TERHADAP PENDAPATAN ASLI DAERAH DENGAN PENERIMAAN SEKTOR PARIWISATA SEBAGAI VARIABEL MODERATING PADA DINAS PARIWISATA KOTA PALEMBANG - Sabrina, Nina; Mudzhalifah, Irma (Balance : Jurnal Akuntansi dan Bisnis, 2018)
The formulation of the problem in this study is how is the influence of the number of tourist objects, the number of tourists and the level of hotel occupancy on local revenue with tourism sector acceptance as a Moderating variable which aims to determine the effect of the number of tourist objects, the number of tourists and hotel occupancy rates on revenue tourism sector as a moderating variable. The type of research used is associative. The independent variables used in this study are the number of attractions, number of tourists and hotel occupancy rates. The dependent variable in this study is regional original income with tourism sector revenue as a moderating variable. Data analysis using multiple linear regression with Pure regression model. The results of this study indicate that the number of tourist objects, number of tourists, and occupancy rates have a significant simultaneous influence on PAD, number of tourist objects, number of tourists, and hotel occupancy rates have a significant influence on PAD with the acceptance of the tourism sector as a variable Moderating; The number of attractions has a simultaneous influence on PAD with the acceptance of the tourism sector as a moderating variable; Acceptance of the Tourism Sector as a Moderating Variable cannot moderate the Number of Tourists towards PAD and Acceptance of the Tourism Sector as a Moderating Variable weakening the influence of Hotel Occupancy Rate on PAD. The number of tourist objects has a significant partial effect on PAD; The number of tourists does not have a significant partial effect on PAD; Hotel Occupancy Rate has a significant influence partially on PAD. It can be concluded that the Acceptance of the Tourism Sector as a moderating variable used in this study actually weakens the relationship between the Number of Attractions, Number of Tourists and Hotel Occupancy Rate as for Regional Original Revenue (PAD)